2018
DOI: 10.1002/pam.22053
|View full text |Cite
|
Sign up to set email alerts
|

Crowd‐Out or Affordability? The Lifeline Expansion's Effect on Wireless Service Spending

Abstract: Public subsidization of private goods often leads to crowd‐out, reducing private spending. This effect is intended for a policy such as the 2008 Lifeline phone subsidy expansion, which aimed to increase affordable access to services. I examine the effects of this policy on households’ self‐reported wireless phone service spending in the Consumer Expenditure Survey. Using state‐level variation in policy implementation and triple‐differences event study methods, I estimate that the expansion reduced households’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…9,10 This includes individuals and families who qualify for Medicaid, Supplemental Nutrition Assistance Program (SNAP), Supplemental Security Income (SSI), and/or Public Housing Agency (PHA) programs. [10][11][12] While these programs address some access issues, barriers still exist in the form of internet related literacy and affordability of internet ready devices. 13 A study conducted by Deloitte 14 found that Medicaid enrollees have increased accessibility to smart phones and tablets, but at a significantly lower rate than employed medically insured persons.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…9,10 This includes individuals and families who qualify for Medicaid, Supplemental Nutrition Assistance Program (SNAP), Supplemental Security Income (SSI), and/or Public Housing Agency (PHA) programs. [10][11][12] While these programs address some access issues, barriers still exist in the form of internet related literacy and affordability of internet ready devices. 13 A study conducted by Deloitte 14 found that Medicaid enrollees have increased accessibility to smart phones and tablets, but at a significantly lower rate than employed medically insured persons.…”
Section: Introduction/backgroundmentioning
confidence: 99%